Assessment of dental professionals' preparedness for treating patients with special health care needs in Lahore, Pakistan - Wajiha Alamgir; Uzma Jabbar Khan; Zubair Maqsood; Sultan Muhammad Sarang; Kashif Siddique (Khyber Medical University Journal)
OBJECTIVE: To evaluate general dentists' perceptions, knowledge, and attitudes regarding the provision of dental services to patients with special health care needs (SHCN).